A Review of Evidence on the Role of Digital Technology in Shaping Attention and Cognitive Control in Children - Vedechkina, Maria; Borgonovi, Francesca (Frontiers in Psychology, 2021)
The role of digital technology in shaping attention and cognitive development has been at the centre of public discourse for decades. The current review presents findings from three main bodies of literature on the implications of technology use for attention and cognitive control: television, video games, and digital multitasking. The aim is to identify key lessons from prior research that are relevant for the current generation of digital users. In particular, the lack of scientific consensus on whether digital technologies are good or bad for children reflects that effects depend on users’ characteristics, the form digital technologies take, the circumstances in which use occurs and the interaction between the three factors. Some features of digital media may be particularly problematic, but only for certain users and only in certain contexts. Similarly, individual differences mediate how, when and why individuals use technology, as well as how much benefit or harm can be derived from its use. The finding emerging from the review on the large degree of heterogeneity in associations is especially relevant due to the rapid development and diffusion of a large number of different digital technologies and contents, and the increasing variety of user experiences. We discuss the importance of leveraging existing knowledge and integrating past research findings into a broader organising framework in order to guide emerging technology-based research and practice. We end with a discussion of some of the challenges and unaddressed issues in the literature and propose directions for future research.